2007
DOI: 10.1080/02568540709594611
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Referral, Evaluation, and Placement Practices for Preschool English Language Learners

Abstract: Made available courtesy of Taylor & Francis (Routledge): http://www.routledge.com/ ***Reprinted with permission. No further reproduction is authorized without written permission from Taylor & Francis (Routledge). This version of the document is not the version of record. Figures and/or pictures may be missing from this format of the document.***

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
9
0
4
Order By: Relevance
“…Then consent forms and demographic forms were explained, signed, and collected before beginning the data collection. Focus group questions were based on the results of the survey project described earlier (Hardin et al 2007). The focus group protocols consisted of open-ended questions regarding: beliefs surrounding educational services for young children, including those with disabilities; current processes used during the referral, evaluation, and placement process; and suggestions for improving these processes for children who are ELLs, particularly from the Latino population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then consent forms and demographic forms were explained, signed, and collected before beginning the data collection. Focus group questions were based on the results of the survey project described earlier (Hardin et al 2007). The focus group protocols consisted of open-ended questions regarding: beliefs surrounding educational services for young children, including those with disabilities; current processes used during the referral, evaluation, and placement process; and suggestions for improving these processes for children who are ELLs, particularly from the Latino population.…”
Section: Methodsmentioning
confidence: 99%
“…Another factor is lack of clarity on the part of professionals about the purpose of screening and assessment instruments. For example, in a statewide survey of early childhood regular and special education professionals, Hardin et al (2007) found that the DIAL-3, a developmental screen, was reported as a language proficiency test (16.7% of administrators, 40% of teachers) as well as a diagnostic assessment (15.4, 20% respectively). Related to this problem is an insufficient number of bilingual professionals and lack of trained interpreters.…”
Section: Background Informationmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, when information is gathered in an inconsistent manner or using instruments that were designed for other purposes (i.e., screening vs. proficiency ratings vs. diagnostics) test results may not converge and/or lead to misidentification (Bracken 1988; Hardin, Roach, and Peisner-Feiberg 2007). Likewise, test translation may change the target construct relative to the original resulting in unintended responses (Fox and Cheng 2007).…”
Section: Using Language Tests and Surveys To Establish Need For Servicesmentioning
confidence: 99%
“…Other researchers have attributed the lack of quality of multi-tiered interventions for ELL students (Wilkinson, Ortiz, Robertson, & Kushner, 2006). Hardin, Roach-Scott, and Peisner-Feinberg (2007) expressed the need of professional preparation for teachers, administrators, and paraprofessionals to appropriately instruct and meet the needs of ELL students.…”
Section: Ells In Special Educationmentioning
confidence: 99%